Effect of Intercropping with Mustard with Onion and Garlic on Aphid Population and Yield - Sarker, PK; Rahman, MM; Das, BC (Journal of Bio-Science, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Field experiments were conducted to study the effect of intercropping of mustard (Brassica napus, Var. Bari Sarisha-7) with onion (Allium cepa L.) and garlic (Allium sativum L.) on aphid [Lipaphis erysimi (Kaltenbach)] population and yield. Intercropped with these two medicinal as well as spice crops reduced the aphid population significantly (P < 0.05). Mustard blocks intercropped with garlic gave highest cost-benefit ratios (1:2.07 and 1: 2.96) than onion intercropped blocks. Sole mustard blocks produced lowest cost-benefit ratios (1:1.65 and 1:2.06). Key words: Intercropping, onion, garlic, agronomic benefits. doi: 10.3329/jbs.v15i0.2200 J. bio-sci. 15: 35-40, 2007